2020
DOI: 10.3389/fmicb.2020.00408
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Structured Biosensors for Monitoring Aflatoxin B1 From Biofilms: A Review

Abstract: Aspergillus exists commonly in many crops and any process of crop growth, harvest, storage, and processing can be polluted by this fungus. Once it forms a biofilm, Aspergillus can produce many toxins, such as aflatoxin B1 (AFB1), ochratoxin, zearalenone, fumonisin, and patulin. Among these toxins, AFB1 possesses the highest toxicity and is labeled as a group I carcinogen in humans and animals. Consequently, the proper control of AFB1 produced from biofilms in food and feed has long been recognized. Moreover, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 92 publications
0
25
0
Order By: Relevance
“…Biosensors circumvent the above-mentioned limitations to ensure a fast in situ analysis [ 19 ]. These kinds of detection techniques exhibit high sensitivity, specificity, excellent performance and are easy-to-use or inexpensive [ 20 ]. Biosensors are desirable for rapid or accurate detection of environmental pollutants, materials, biological and chemical stuff [ 21 ].…”
Section: Biosensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Biosensors circumvent the above-mentioned limitations to ensure a fast in situ analysis [ 19 ]. These kinds of detection techniques exhibit high sensitivity, specificity, excellent performance and are easy-to-use or inexpensive [ 20 ]. Biosensors are desirable for rapid or accurate detection of environmental pollutants, materials, biological and chemical stuff [ 21 ].…”
Section: Biosensorsmentioning
confidence: 99%
“…Most common BREs include aptamers, enzymes, molecularly imprinted polymers, antibodies, and many more. These BREs are known to have high specificity and selectivity for their specific targets [ 20 ]. The STE is used to detect any interactions between the two affinity-pairing partners and thus converts the biological signals into useful electrical signals [ 18 ].…”
Section: Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first aptamer for mycotoxins was that reported by Neoventures Biotechnology Inc. (Canada) for ochratoxin A (OTA) [ 14 ]; next, three different research groups reported other ssDNA sequences candidates for OTA [ 15 , 16 , 17 ]. Furthermore, in addition to the first aptamer for aflatoxin B1 (AFB1) selected by the same company Neoventures Biotechnology [ 18 ], further aptamer sequences were described for AFB1 by other research groups [ 19 , 20 , 21 , 22 , 23 , 24 ]. Similarly, in addition to the first aptamer for fumonisin B1 (FB1) selected by McKeague et al [ 25 ], new aptamer sequences were selected and described by other research groups [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%